Mindfulness intervention in futsal training improves passing accuracy and consistency in extracurricular activities - Dewantoro, Nova Dwi (Universitas Suryakancana, 2025)
This study aims to examine the effectiveness of mindfulness intervention in futsal training on improving the accuracy and consistency of passing among extracurricular participants at SD Negeri Kunti, Bungkal Subdistrict, Ponorogo Regency. The method employed was a quasi-experimental design using a pretest-posttest approach. The subjects consisted of 20 students who regularly participated in futsal extracurricular activities. Based on the data analysis of triangle passing skills, the pretest score was 10.35, while the posttest score increased to 13.55. For wall passing skills, the pretest score was 11.95 and increased to 14.50 in the posttest. The significance value for the triangle passing pretest was 0.109 and for the posttest was 0.022. For wall passing, the significance value for the pretest was 0.123 and for the posttest was 0.013. Using a significance level of ? = 0.05, it can be concluded that the pretest data for both triangle passing and wall passing had significance values greater than 0.05, indicating a normal distribution. However, the posttest data for both triangle passing and wall passing had significance values less than 0.05, indicating a non-normal distribution. Therefore, further inferential analysis was conducted using the non-parametric Wilcoxon signed-rank test. The results showed significant differences between pretest and posttest scores, both in the triangle passing group (Z = -3.745; p = 0.000) and in the wall passing group (Z = -3.746; p = 0.000). These findings indicate that mindfulness intervention effectively enhances students’ passing performance in terms of both accuracy and consistency.